Postcrystallization metasomatism in shergottites: Evidence from the paired meteorites LAR 06319 and LAR 12011. (15th March 2016) - Howarth, Geoffrey H.; Liu, Yang; Chen, Yang; Pernet‐Fisher, John F.; Taylor, Lawrence A.
Abstract: Apatite is the major volatile‐bearing phase in Martian meteorites, containing structurally bound fluorine, chlorine, and hydroxyl ions. In apatite, F is more compatible than Cl, which in turn is more compatible than OH. During degassing, Cl strongly partitions into the exsolved phase, whereas F remains in the melt. For these reasons, the volatile concentrations within apatite are predictable during magmatic differentiation and degassing. Here, we present compositional data for apatite and merrillite in the paired enriched, olivine‐phyric shergottites LAR 12011 and LAR 06319. In addition, we calculate the relative volatile fugacities of the parental melts at the time of apatite formation. The apatites are dominantly OH‐rich (calculated by stoichiometry) with variable yet high Cl contents. Although several other studies have found evidence for degassing in the late‐stage mineral assemblage of LAR 06319, the apatite evolutionary trends cannot be reconciled with this interpretation. The variable Cl contents and high OH contents measured in apatites are not consistent with fractionation either. Volatile fugacity calculations indicate that water and fluorine activities remain relatively constant, whereas there is a large variation in the chlorine activity. The Martian crust is Cl‐rich indicating that changes in Cl contents in the apatites may be related to an external crustal source. We suggest that the high and variable Cl contents and high OH contents of the apatite are the results of postcrystallization interaction with Cl‐rich, and possibly water‐rich, crustal fluids circulating in the Martian crust.